Pengaruh Budaya Organisasi Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Arddy Mitra Karya Serpong Kota Tangerang Selatan - Debi Mega Riski; Fahmi Susanti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the effect of organizational culture and the physical work environment on employee performance at PT Arddy Mitra Karya Serpong, South Tangerang. This research uses a quantitative approach with a survey method. The population consists of 50 employees of PT Arddy Mitra Karya Serpong and a saturated sampling technique was applied so that the entire population became respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The t-test results indicate that organizational culture has a positive and significant effect on employee performance (t = 4.699 > t-table = 2,012; p = 0.000 < 0.05) and the physical work environment also has a positive and significant effect (t = 4.095 > t-table = 2,012; p = 0.000 < 0.05). Simultaneously, the F-test confirms a significant joint effect of organizational culture and the physical work environment on employee performance (F = 59.574 > F-table = 3,195; p = 0.000 < 0.05). These findings imply that strengthening organizational culture values and continuously improving the physical work environment can optimally enhance employee performance